A CLINICAL STUDY OF VARIOUS PATTERNS OF ABDOMINAL WALL HERNIA WITH SPECIAL EMPHASIS ON INGUINAL HERNIA AND IT’S CORRELATION WITH PRE-OPERATIVE ULTRASONOGRAPHY AND INTRAOPERATIVE FINDINGS AT TERTIARY CARE CENTRE - Saran, Tejpal Singh; SP, Chouhan; Singh, Harpinder (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Various presentations of abdominal wall hernia and their clinical correlation to preoperative ultrasonography report and intraoperative findings. Methods: Fifty consecutive patients were admitted to the Department of General Surgery at PMCH, Udaipur, during January 2021–June 2022, with a mean follow-up period of 18 months. The patient’s particulars, elaborate h/o complaints, clinical examination, investigations, procedure done, and post-operative complications were recorded. Results: Maximum cases reported had a right inguinal hernia, hence right inguinal hernioplasty was performed in 46% of cases, followed by left inguinal hernioplasty in 32%, bilateral inguinal hernioplasty in 14%, and epigastric and mesh hernioplasty in 4% each. The judgemental accuracy and of ultrasound (USG) had sensitivity of 86.96%, specificity of 100.00%, and accuracy of 88.00%. Intraoperatively, 92% of sonography findings were confirmed. In only six cases, the findings differed from ultrasound. Conclusion: High-resolution sonography is an accurate diagnostic imaging modality in anterior abdominal wall lesions. The advantages of high-resolution sonography include noninvasiveness, high accuracy, lack of ionizing radiation, simplicity, wide availability, cost-effectiveness, and repeatability.